Servant Leader: A New Paradigm - Taylor V., John Wesley (2012)
Leadership that one adopts is based on their Worldviews and in his outlook on life.The worldview of the Samaritan told by Christ (Luke 10:30-36) and it leads to aparadigm shift in the life of a leader.In a situation “what can I win” to other “whatcan I give”. In this article discusses the prospects and biblical proportions ServantLeader, and taking Christ as the perfect model of a servant Leader.